Immunomodulation—What to Modulate and Why? Potential Immune Targets - Quach, Su Sheng; Zhu, Alan; Lee, Ryan S. B.; Seymour, Gregory J. (Frontiers in Dental Medicine, 2022)
Despite over 50 years of research into the immunology of periodontal disease, the precise mechanisms and the role of many cell types remains an enigma. Progress has been limited by the inability to determine disease activity clinically. Understanding the immunopathogenesis of periodontal disease however is fundamental if immunomodulation is to be used as a therapeutic strategy. It is important for the clinician to understand what could be modulated and why. In this context, potential targets include different immune cell populations and their subsets, as well as various cytokines. The aim of this review is to examine the role of different immune cell populations and their cytokines in the pathogenesis of periodontal disease and their potential as possible therapeutic targets.